Evaluating the Influence of Basel Accord on Banking Sector of Pakistan (Journal of Asian Development Studies, 2024)
The papers aim to investigate how Basel III affected Pakistan's entire banking sector from 2013 to 2018. The requirements and obligations of Basel III are regarded as the most efficient tools for the banking sector. When analyzing the impact of Basel III on the banking industry, three primary considerations are made: financial size, spread, and provision for non-performing loans. Relapse investigations were utilized for checking speculation. We inferred that the general pummel of Basel III on banks is enormous, yet not all banks have totally taken on Basel III. The significance of this research lies in giving important experiences into the viability of global regulatory structures in rising economies' potential. By evaluating the Basel Accord's effect on Pakistan's banking sector, this study adds to a more extensive comprehension of how worldwide guidelines can be adjusted to neighborhood settings and how they can address explicit challenges faced by banks in emerging nations. This analysis not only reveals insight into the operational and vital changes made by Pakistani banks but also gives suggestions for policymakers to upgrade regulatory practices and monetary strength. Eventually, this research aims to illuminate future regulatory changes and work on the flexibility of Pakistan's banking sector in the face of worldwide monetary uncertainties. We propose highlighting semiannually the effects of Basel on the banking industry and conducting a comparison analysis of conventional and Islamic banks.